Lead-containing soldering paste capable of preventing tin explosion and preparation method of lead-containing soldering paste

By adding polyacrylic acid intercalation hydrotalcite and nano-silica to lead solder paste, the problem of tin frying during the soldering process is solved, the solder stability and reliability are improved, and the high quality and safety of solder joints are ensured. .

CN119175495AInactive Publication Date: 2024-12-24深圳市华远金属有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411301791.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lead solder paste is prone to tin frying during the soldering process, resulting in a decrease in solder joint quality, reduced product reliability and safety hazards.

Method used

The lead solder paste formula containing polyacrylic acid intercalated hydrotalcite and nano-silica is adopted. Through specific raw material composition and ratio, the moisture content in the solder paste is reduced, the soldering stability and wettability are improved, and the tin frying phenomenon is prevented. The occurrence of

Benefits of technology

It effectively prevents the occurrence of tin frying, improves the welding quality and durability of solder joints, and ensures the stability and reliability of the welding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005047873180000071
    Figure BDA0005047873180000071
  • Figure BDA0005047873180000081
    Figure BDA0005047873180000081
Patent Text Reader

Abstract

The invention relates to the technical field of soldering paste. The invention discloses lead-containing soldering paste capable of preventing tin explosion and a preparation method of the lead-containing soldering paste. The lead-containing soldering paste is prepared from the following raw materials: lead soldering powder, soldering flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide, the soldering flux comprises the following raw materials: rosin, an active agent, a surfactant, a thixotropic agent, a corrosion inhibitor, a film-forming agent and a solvent. The preparation method comprises the following steps: mixing rosin, an active agent and a solvent, stirring at 150-160 DEG C for 0.5-1 hour, and cooling to 30-50 DEG C to prepare a premixed solution; a surface active agent, a thixotropic agent, a film-forming agent and a corrosion inhibitor are sequentially added into the premixed liquid, stirring and mixing are conducted, and scaling powder is prepared; the soldering flux, the polyacrylic acid intercalated hydrotalcite, the nano silicon dioxide and the lead-containing soldering tin powder are stirred and mixed, and the lead-containing soldering tin paste capable of preventing tin explosion is prepared. The lead-containing soldering paste prepared by the invention can effectively prevent tin explosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solder paste, and in particular to an explosion-proof lead solder paste and a preparation method thereof. Background Art

[0002] Solder paste is a welding material used in electronic assembly. It is mainly used in surface mount technology (SMT) to fix electronic components (such as resistors, capacitors, integrated circuits, etc.) on printed circuit boards (PCBs). As the main solder, the performance of solder paste is directly related to the reliability of welding and product quality.

[0003] At present, there are two main types of solder paste on the market: lead solder paste and lead-free solder paste. Lead solder paste is widely used due to its lower melting point, good fluidity and stable soldering effect. This type of solder paste is easy to solder, has good fluidity, and can better wet the soldered surface to form beautiful and reliable solder joints. In addition, due to its lower melting point, lead solder paste allows a larger temperature range during the soldering process, reducing soldering defects caused by improper temperature control, such as voids, bridging and other problems.

[0004] Although lead solder paste has obvious performance advantages, it also has some obvious limitations. One of the most prominent problems is the phenomenon of tin explosion, which is the sudden explosion or splash of solder paste during the soldering process. Tin explosion is mainly caused by the rapid vaporization of water contained in the solder paste or PCB board at high temperature to form vapor pressure. This phenomenon not only affects the quality of welding, but also causes bubbles to form in the solder joint, reducing the strength and conductivity of the solder joint; at the same time, tiny solder beads may appear around the solder joint, which may cause short circuits or reduce the overall reliability of the product. In addition, the high-speed airflow and splashing solder generated by tin explosion may damage sensitive electronic components, reduce production efficiency, and bring safety hazards.

[0005] Therefore, there is an urgent need to develop a lead solder paste that is tin-proof and can effectively prevent the occurrence of tin explosion while maintaining the existing advantages. Summary of the invention

[0006] In order to solve at least one of the above technical problems, a lead solder paste with anti-tin explosion is developed. The present application provides a lead solder paste with anti-tin explosion and a preparation method thereof.

[0007] On the one hand, the present application provides an explosion-proof lead solder paste, comprising lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano-silicon dioxide, wherein the weight ratio of the lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano-silicon dioxide is 85-90:10-15:1-2:0.5-1; The soldering flux comprises, by mass percentage, 30% to 40% rosin, 5% to 10% activator, 1% to 5% surfactant, 4% to 10% thixotropic agent, 1% to 5% corrosion inhibitor, 1% to 3% film former, and the balance is solvent.

[0008] By adopting the above technical solution, the present application adopts specific raw materials and proportions, and the lead solder paste prepared can reduce the moisture content in the solder paste, improve its stability and reliability during the welding process, effectively prevent tin frying, and have good wettability. The present application adds polyacrylic acid intercalated hydrotalcite and nano-silicon dioxide, which can effectively absorb moisture in the solder paste and reduce the occurrence of tin frying. The polyacrylic acid intercalated hydrotalcite can also improve the thermal stability and chemical stability of the solder paste.

[0009] The activator and surfactant in the flux of the present application can improve the wettability and cleaning effects, thereby improving the welding quality; the thixotropic agent can improve the rheology of the solder paste, making it easier to control during the printing process; the corrosion inhibitor provides protection in the early stage of welding; the film-forming agent can form a protective film to prevent oxidation of the solder joint and improve the durability of the solder joint.

[0010] Optionally, the lead solder powder is Sn63Pb37, and the average particle size is 30-45 μm.

[0011] By adopting the above technical solution, the lead solder powder Sn63Pb37 has a relatively low melting point and good fluidity, and is suitable for the welding of most electronic components.

[0012] Optionally, the preparation method of the polyacrylic acid intercalated hydrotalcite is: Step 1: Mix Mg(NO3)2·6H2O and Al(NO3)3·9H2O, add water to dissolve, and prepare a mixed salt solution; Mg 2+ and Al 3+ The molar ratio is 2 to 3:1; Step 2: adding a sodium hydroxide solution dropwise to the mixed salt solution, stirring to generate a precipitate, separating, washing, and drying to obtain a basic hydrotalcite; Step 3: ultrasonically dispersing the basic hydrotalcite in water to obtain a hydrotalcite suspension; Step 4: adding polyacrylic acid to the hydrotalcite suspension, adding potassium persulfate, stirring, separating, washing, and drying to obtain polyacrylic acid intercalated hydrotalcite.

[0013] By adopting the above technical solution, the polyacrylic acid intercalated hydrotalcite can enhance stability and absorb moisture in the solder paste to prevent tin frying.

[0014] Optionally, the average particle size of the nano-silicon dioxide is 10 to 50 nm.

[0015] By adopting the above technical solution, the nano silicon dioxide of the present application has good dispersibility, and the appropriate average particle size can improve the rheology of the solder paste and enhance its thixotropy.

[0016] Optionally, the weight ratio of the polyacrylic acid intercalated hydrotalcite to nano-silicon dioxide is 1.5 to 3:1.

[0017] By adopting the above technical solution, the polyacrylic acid intercalated hydrotalcite and nano-silicon dioxide of the present application work together to improve the stability of solder paste and reduce the tin explosion phenomenon.

[0018] Optionally, the active agent is selected from at least one of citric acid, p-toluenesulfonic acid, sulfosalicylic acid and lactic acid.

[0019] By adopting the above technical solution, the active agent of the present application can accelerate the dissolution of oxides and increase the wetting speed, thereby improving the wettability and welding quality during the welding process.

[0020] Optionally, the active agent is citric acid, p-toluenesulfonic acid and sulfosalicylic acid, and the weight ratio of the citric acid, p-toluenesulfonic acid and sulfosalicylic acid is 1:2:2.

[0021] By adopting the above technical solution, the specific ratio of the active agent in the present application can balance the different performance characteristics of the active agent, ensuring that it can effectively remove oxides and provide sufficient wettability while maintaining the stability of the flux.

[0022] Optionally, the surfactant is selected from at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and nonylphenol polyoxyethylene ether.

[0023] Optionally, the thixotropic agent is selected from at least one of ethylene bisstearamide, hydroxyethyl cellulose and hydrogenated castor oil; The corrosion inhibitor is selected from at least one of triethanolamine, sodium nitrite and 2-pentylbenzimidazole.

[0024] By adopting the above technical solution, the thixotropic agent of the present application can improve the rheology and stability of the solder paste, which helps to maintain the shape of the solder joint; the corrosion inhibitor can protect the solder joint from corrosion after welding and improve the long-term stability of the solder joint.

[0025] Optionally, the film-forming agent is selected from at least one of polyvinyl butyral, polyvinyl pyrrolidone and PEG-4000; The solvent is selected from at least one of water, methanol, ethanol and propylene glycol.

[0026] By adopting the above technical solution, the film-forming agent of the present application can protect the solder joints from oxidation and corrosion.

[0027] In a second aspect, the present application provides a method for preparing the above-mentioned explosion-proof lead solder paste, comprising the following steps: S1, mixing the rosin, the activator and the solvent, stirring at 150-160° C. for 0.5-1 h, and cooling to 30-50° C. to obtain a premixed solution; S2, adding the surfactant, thixotropic agent, film-forming agent and corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, to obtain a soldering flux; S3, stirring and mixing the soldering flux, polyacrylic acid intercalated hydrotalcite, nano silicon dioxide and lead solder powder to prepare an explosion-proof lead solder paste.

[0028] By adopting the above technical solution, the preparation method of the present application is simple to operate and has high preparation efficiency. The present application gradually mixes the raw materials, which can make the components of the flux evenly dispersed, improve the overall performance of the solder paste, and effectively reduce the occurrence of tin explosion. The preparation process is energy-saving and emission-reducing, and pollution-free.

[0029] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The lead solder paste prepared by the application using specific raw materials and proportions can reduce the moisture content in the solder paste, improve its stability and reliability during the welding process, effectively prevent tin frying, and has good wettability.

[0030] 2. The present application adds polyacrylic acid intercalated hydrotalcite and nano-silicon dioxide, which can effectively absorb moisture in the solder paste and reduce the occurrence of tin frying.

[0031] 3. The preparation method of the present application is simple to operate and has high preparation efficiency. The present application gradually mixes the raw materials, which can evenly disperse the components of the flux, improve the overall performance of the solder paste, and effectively reduce the occurrence of tin explosion. DETAILED DESCRIPTION

[0032] The present application is further described in detail below with reference to the embodiments.

[0033] The present application designs a lead solder paste for preventing tin explosion, comprising lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide, wherein the weight ratio of the lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide is 85-90:10-15:1-2:0.5-1; The soldering flux comprises, by mass percentage, 30% to 40% rosin, 5% to 10% activator, 1% to 5% surfactant, 4% to 10% thixotropic agent, 1% to 5% corrosion inhibitor, 1% to 3% film former, and the balance is solvent.

[0034] The lead solder paste of the present application for preventing explosion of tin is prepared by the following method, comprising the following steps: S1, mixing the rosin, the activator and the solvent, stirring at 150-160° C. for 0.5-1 h, and cooling to 30-50° C. to obtain a premixed solution; S2, adding the surfactant, thixotropic agent, film-forming agent and corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, to obtain a soldering flux; S3, stirring and mixing the soldering flux, polyacrylic acid intercalated hydrotalcite, nano silicon dioxide and lead solder powder to prepare an explosion-proof lead solder paste.

[0035] The present application designs a technical solution to address the problem that existing lead solder paste may cause tin frying during the welding process, thereby affecting the welding quality.

[0036] The raw materials used in this application are as follows: Mg(NO3)2·6H2O (magnesium nitrate hexahydrate): CAS: 13446-18-9.

[0037] Al(NO3)3·9H2O (aluminum nitrate nonahydrate): CAS: 7784-27-2.

[0038] Polyacrylic acid: CAS: 9003-01-4.

[0039] Potassium persulfate: CAS: 7727-21-1.

[0040] Rosin: CAS: 8050-09-7.

[0041] Citric acid: CAS: 77-92-9.

[0042] p-Toluenesulfonic acid: CAS: 104-15-4.

[0043] Sulfosalicylic acid: CAS: 5965-83-3.

[0044] Sodium dodecyl sulfate: CAS: 151-21-3.

[0045] Nonylphenol polyoxyethylene ether: CAS: 127087-87-0.

[0046] Ethylene bisstearamide: CAS: 110-30-5.

[0047] Hydroxyethyl cellulose: CAS: 9004-62-0.

[0048] Triethanolamine: CAS: 102-71-6.

[0049] 2-Pentylbenzimidazole: CAS: 5851-46-7.

[0050] Polyvinyl butyral: CAS: 63148-65-2.

[0051] Polyvinylpyrrolidone: CAS: 9003-39-8.

[0052] Ethanol: CAS: 64-17-5. Specific embodiments

[0053] The preparation method of the polyacrylic acid intercalated hydrotalcite used in Examples 1 to 3 is: Step 1: Mix Mg(NO3)2·6H2O and Al(NO3)3·9H2O, add water to dissolve, and prepare a mixed salt solution; Mg 2+ and Al 3+ The molar ratio is 3:1; Step 2: adding a sodium hydroxide solution with a mass fraction of 5 wt% dropwise to the mixed salt solution, stirring to generate a precipitate, separating, washing, and drying to obtain a basic hydrotalcite; Step 3: ultrasonically dispersing the basic hydrotalcite in water to obtain a hydrotalcite suspension; Step 4: adding polyacrylic acid to the hydrotalcite suspension, adding potassium persulfate, stirring at 70° C. for 7 hours, separating, washing, and drying to obtain polyacrylic acid intercalated hydrotalcite; the weight ratio of polyacrylic acid to basic hydrotalcite is 1:10.

[0054] Examples 1 to 3 Example 1 This embodiment provides a lead solder paste for preventing tin explosion, comprising lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide, wherein the weight ratio of the lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide is 85:10:1:0.5; The flux is composed of raw materials by mass percentage: rosin 30%, activator 10%, surfactant 1%, thixotropic agent 10%, corrosion inhibitor 1%, film former 3%, and the balance is solvent; Among them, the lead solder powder is Sn63Pb37, with an average particle size of 40μm; the average particle size of nano-silicon dioxide is 30nm; the active agent is sulfosalicylic acid; the surfactant is sodium dodecyl sulfate; the thixotropic agent is ethylene bisstearamide; the corrosion inhibitor is 2-pentylbenzimidazole; the film-forming agent is polyvinyl butyral; and the solvent is water.

[0055] The preparation method comprises the following steps: S1. Mix rosin, active agent and solvent, stir at 150°C for 1h, and cool to 30°C to prepare a premixed solution; S2, adding a surfactant, a thixotropic agent, a film-forming agent, and a corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, and preparing a soldering flux; S3, mixing flux, polyacrylic acid intercalated hydrotalcite, nano silicon dioxide and lead solder powder to prepare anti-explosion lead solder paste.

[0056] Example 2 This embodiment provides a lead solder paste for preventing tin explosion, comprising lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide, wherein the weight ratio of lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide is 88:13:1.5:0.8; The flux is composed of raw materials by mass percentage: rosin 35%, activator 8%, surfactant 3%, thixotropic agent 7%, corrosion inhibitor 3%, film former 2%, and the balance is solvent; Among them, the lead solder powder is Sn63Pb37, with an average particle size of 40μm; the average particle size of nano-silicon dioxide is 30nm; the active agent is sulfosalicylic acid; the surfactant is sodium dodecyl sulfate; the thixotropic agent is ethylene bisstearamide; the corrosion inhibitor is 2-pentylbenzimidazole; the film-forming agent is polyvinyl butyral; and the solvent is water.

[0057] The preparation method comprises the following steps: S1. Mix rosin, activator and solvent, stir at 155°C for 0.8h, and cool to 40°C to prepare a premixed solution; S2. Adding surfactant, thixotropic agent, film-forming agent and corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, and preparing flux; S3. Stirring and mixing the flux, polyacrylic acid intercalated hydrotalcite, nano-silica and lead solder powder, and preparing anti-explosion lead solder paste.

[0058] Example 3 This embodiment provides a lead solder paste for preventing tin explosion, comprising lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide, wherein the weight ratio of the lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide is 90:15:2:1; The flux is composed of raw materials in percentage by mass: rosin 40%, activator 5%, surfactant 5%, thixotropic agent 4%, corrosion inhibitor 5%, film former 1%, and the balance is solvent; Among them, the lead solder powder is Sn63Pb37, with an average particle size of 40μm; the average particle size of nano-silicon dioxide is 30nm; the active agent is sulfosalicylic acid; the surfactant is sodium dodecyl sulfate; the thixotropic agent is ethylene bisstearamide; the corrosion inhibitor is 2-pentylbenzimidazole; the film-forming agent is polyvinyl butyral; and the solvent is water.

[0059] The preparation method comprises the following steps: S1. Mix rosin, activator and solvent, stir at 160°C for 0.5h, and cool to 50°C to prepare a premixed solution; S2. Adding surfactant, thixotropic agent, film-forming agent and corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, and preparing flux; S3. Stirring and mixing the flux, polyacrylic acid intercalated hydrotalcite, nano-silica and lead solder powder, and preparing anti-explosion lead solder paste.

[0060] Comparative Examples 1 to 5 Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that, in Comparative Example 1, no polyacrylic acid intercalated hydrotalcite and nano-silica are added.

[0061] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that no polyacrylic acid intercalated hydrotalcite is added in Comparative Example 2.

[0062] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that no nano silicon dioxide is added in Comparative Example 3.

[0063] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that in Comparative Example 4, the polyacrylic acid intercalated hydrotalcite is replaced with an equal weight of basic hydrotalcite, and the preparation method of the basic hydrotalcite is: Step 1: Mix Mg(NO3)2·6H2O and Al(NO3)3·9H2O, add water to dissolve, and prepare a mixed salt solution; Mg 2+ and Al 3+ The molar ratio is 3:1; Step 2: adding a sodium hydroxide solution with a mass fraction of 5 wt% dropwise into the mixed salt solution, stirring to generate a precipitate, separating, washing, and drying to obtain a basic hydrotalcite.

[0064] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that the preparation method of the solder paste in Comparative Example 5 is: S1. Mix rosin, activator, solvent, surfactant, thixotropic agent, film former and corrosion inhibitor, stir at 155°C for 0.8h, and cool to 40°C to obtain flux; S2. The flux, polyacrylic acid intercalated hydrotalcite, nano silicon dioxide and lead solder powder are stirred and mixed to prepare an explosion-proof lead solder paste.

[0065] Experimental testing Test items and methods: Test the expansion rate of solder paste according to JIS Z3284; Assess the solder bead level according to the solder bead test assessment standard in SJ / T 11186-2019 "General Specification for Solder Paste"; Solder joint morphology: Place the solder paste sample at room temperature and 90% relative humidity for 10 hours, then perform soldering to observe whether tin frying occurs during welding and the solder joint morphology after welding.

[0066] The anti-explosion lead solder pastes prepared in Examples 1 to 3 and Comparative Examples 1 to 5 were tested for expansion rate, solder bead level, tin explosion phenomenon and solder joint morphology. The test results are shown in Table 1.

[0067] Table 1 From the test results in Table 1, it can be seen that the lead solder pastes prepared in Examples 1 to 3 can effectively prevent tin explosion, have a high expansion rate, good wettability, the solder bead level is all level 1, the solder joints are regular in shape, and the solder joints are full.

[0068] The lead solder pastes prepared in Comparative Examples 1 to 3 have a significantly reduced expansion rate, tin beads of level 2 to 3, tin frying, irregular solder joint shapes, and incomplete solder joints.

[0069] In Comparative Example 4, the polyacrylic acid intercalated hydrotalcite was replaced with an equal weight of basic hydrotalcite, and the expansion rate of the obtained lead solder paste decreased.

[0070] Comparative Example 5: The flux raw materials are mixed in one step to obtain a lead solder paste, which has a reduced expansion rate, a tin bead level 2, an irregular shape, and insufficiently full solder joints.

[0071] Embodiments 4 to 15 Example 4 The difference between Example 4 and Example 2 is that in Example 4, the average particle size of nano-silicon dioxide is 10 nm.

[0072] Example 5 The difference between Example 5 and Example 2 is that in Example 5, the average particle size of nano-silicon dioxide is 50 nm.

[0073] Example 6 The difference between Example 6 and Example 2 is that in Example 6, the weight ratio of polyacrylic acid intercalated hydrotalcite and nano-silica is 1.5:1, and the total proportion of polyacrylic acid intercalated hydrotalcite and nano-silica is 2.3.

[0074] Example 7 The difference between Example 7 and Example 2 is that in Example 7, the weight ratio of polyacrylic acid intercalated hydrotalcite and nano-silica is 3:1, and the total proportion of polyacrylic acid intercalated hydrotalcite and nano-silica is 2.3.

[0075] Example 8 The difference between Example 8 and Example 2 is that the active agent in Example 8 is p-toluenesulfonic acid and sulfosalicylic acid in a weight ratio of 1:1:1.

[0076] Example 9 The difference between Example 9 and Example 2 is that the active agent in Example 9 is citric acid, p-toluenesulfonic acid and sulfosalicylic acid in a weight ratio of 1:1:1.

[0077] Example 10 The difference between Example 10 and Example 2 is that the active agent in Example 10 is citric acid, p-toluenesulfonic acid and sulfosalicylic acid in a weight ratio of 1:2:2.

[0078] Embodiment 11 The difference between Example 11 and Example 10 is that in Example 11, the surfactant is nonylphenol polyoxyethylene ether.

[0079] Example 12 The difference between Example 12 and Example 10 is that in Example 12, the thixotropic agent is hydroxyethyl cellulose.

[0080] Embodiment 13 The difference between Example 13 and Example 10 is that in Example 13, the corrosion inhibitor is triethanolamine.

[0081] Embodiment 14 The difference between Example 14 and Example 10 is that in Example 14, the film-forming agent is polyvinyl pyrrolidone.

[0082] Embodiment 15 The difference between Example 15 and Example 10 is that in Example 15, the solvent is ethanol.

[0083] The anti-explosion lead solder paste prepared in Examples 4 to 15 was tested for expansion rate, solder bead level, tin explosion phenomenon and solder joint morphology. The test results are shown in Table 2.

[0084] Table 2 Expansion rate / % Solder bead level Whether there is tinning Solder joint morphology Example 4 92.5 1 none Regular shape, full solder joints Example 5 92.0 1 none Regular shape, full solder joints Example 6 91.8 1 none Regular shape, full solder joints Example 7 92.3 1 none Regular shape, full solder joints Example 8 93.1 1 none Regular shape, full solder joints Example 9 93.7 1 none Regular shape, full solder joints Example 10 94.0 1 none Regular shape, full solder joints Embodiment 11 94.1 1 none Regular shape, full solder joints Example 12 93.9 1 none Regular shape, full solder joints Embodiment 13 94.0 1 none Regular shape, full solder joints Embodiment 14 94.2 1 none Regular shape, full solder joints Embodiment 15 94.0 1 none Regular shape, full solder joints From the test results in Table 2, it can be seen that the difference between Example 4 and Example 5 and Example 2 is that the average particle size of the nano-silicon dioxide is different, among which the expansion rate of the lead solder paste prepared in Example 2 is the highest.

[0085] The difference between Example 6 and Example 7 and Example 2 is that the weight ratios of polyacrylic acid intercalated hydrotalcite and nano-silica are different, and the expansion rate of the lead solder paste prepared in Example 2 is the highest.

[0086] The expansion rate of the lead solder paste prepared in Example 8 is increased, and the expansion rate of the lead solder paste prepared in Example 9 is increased more significantly. Among Examples 8 to 10, the expansion rate of the lead solder paste prepared in Example 10 is the best.

[0087] The properties of the lead solder pastes prepared in Examples 11 to 15 are similar.

[0088] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A lead solder paste for preventing tin explosion, characterized in that: The invention comprises lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide, wherein the weight ratio of the lead solder powder, flux, polyacrylic acid intercalated hydrotalcite and nano silicon dioxide is 85-90:10-15:1-2:0.5-1; The soldering flux comprises, by mass percentage, 30% to 40% rosin, 5% to 10% activator, 1% to 5% surfactant, 4% to 10% thixotropic agent, 1% to 5% corrosion inhibitor, 1% to 3% film former, and the balance is solvent.

2. The lead solder paste for preventing explosion of tin according to claim 1, characterized in that: The preparation method of the polyacrylic acid intercalated hydrotalcite is: Step 1: Mix Mg(NO3)2·6H2O and Al(NO3)3·9H2O, add water to dissolve, and prepare a mixed salt solution; Mg 2+ and Al 3+ The molar ratio is 2~3:1; Step 2: adding sodium hydroxide solution dropwise to the mixed salt solution, stirring to generate precipitation, separating, washing, and drying to obtain basic hydrotalcite; Step 3: ultrasonically dispersing the basic hydrotalcite in water to obtain a hydrotalcite suspension; Step 4: adding polyacrylic acid to the hydrotalcite suspension, adding potassium persulfate, stirring, separating, washing, and drying to obtain polyacrylic acid intercalated hydrotalcite.

3. The lead solder paste for preventing explosion of tin according to claim 1, characterized in that: The average particle size of the nano silicon dioxide is 10-50 nm.

4. The lead solder paste for preventing explosion of tin according to claim 1, characterized in that: The weight ratio of the polyacrylic acid intercalated hydrotalcite to nano silicon dioxide is 1.5-3:

1.

5. The lead solder paste for preventing explosion of tin according to claim 1, characterized in that: The active agent is selected from at least one of citric acid, p-toluenesulfonic acid, sulfosalicylic acid and lactic acid.

6. The lead solder paste for preventing explosion of tin according to claim 5, characterized in that: The active agent is citric acid, p-toluenesulfonic acid and sulfosalicylic acid, and the weight ratio of the citric acid, p-toluenesulfonic acid and sulfosalicylic acid is 1:2:

2.

7. The lead solder paste for preventing explosion of tin according to claim 1, characterized in that: The surfactant is selected from at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate and nonylphenol polyoxyethylene ether.

8. The anti-explosion lead solder paste according to claim 1, characterized in that: The thixotropic agent is selected from at least one of ethylene bisstearamide, hydroxyethyl cellulose and hydrogenated castor oil; The corrosion inhibitor is selected from at least one of triethanolamine, sodium nitrite and 2-pentylbenzimidazole.

9. The lead solder paste for preventing tin explosion according to claim 1, characterized in that: The film-forming agent is selected from at least one of polyvinyl butyral, polyvinyl pyrrolidone and PEG-4000; The solvent is selected from at least one of water, methanol, ethanol and propylene glycol.

10. A method for preparing the explosion-proof lead solder paste according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing the rosin, the activator and the solvent, stirring at 150-160° C. for 0.5-1 h, and cooling to 30-50° C. to obtain a premixed solution; S2, adding the surfactant, thixotropic agent, film-forming agent and corrosion inhibitor to the premixed liquid in sequence, stirring and mixing, to obtain a soldering flux; S3, stirring and mixing the soldering flux, polyacrylic acid intercalated hydrotalcite, nano silicon dioxide and lead solder powder to prepare an explosion-proof lead solder paste.

Citation Information

Cited By

  • Flux paste for solder paste

    CN119681495A